Island ecosystem responses to the Kuwae eruption and precipitation change over the last 1600 years, Efate, Vanuatu - Strandberg, Nichola A.; Sear, David A.; Langdon, Peter G.; Cronin, Shane J.; Langdon, Catherine T.; Maloney, Ashley E.; Bateman, Samantha L.; Bishop, Thomas; Croudace, Ian W.; Leng, Melanie J.; Sachs, Julian P.; Prebble, Matiu; et al. (Frontiers in Ecology and Evolution, 2023)
Islands of the Southwest Pacific are exposed to geologic and climate-related disturbances that occur on a range of timescales and which probably affect, to varying degrees, their terrestrial ecosystems. Over the past 11000 years we know of two major events in the region: the Kuwae eruption which is thought to have occurred of 500–510 cal. years BP and a shift to drier conditions which began 1100 cal. years BP. We investigated terrestrial and lacustrine ecosystem responses to these events and also to a changing fire regime, likely human-caused, using a multi-proxy (C/N, charcoal, chironomids, pollen, and tephra) record from Lake Emaotul, Efate, Vanuatu. Tephra from the Kuwae eruption was found across a 6 cm layer which our age-depth model suggests was deposited 650–510 cal. years BP (95% confidence). Forest and chironomid community turnover increased during the wet-dry shift 1100–1000950 cal. years BP; subsequently, chironomid turnover rates decreased again within <135215 years and vegetation had partially (but not fully) recovered after 870 years. Following Kuwae volcanic tephraash deposition, vegetation turnover increased again, reflecting a reduction in small trees and shrubs and an increase in grasses. Subsequently, the forest vegetation did not regain its previous composition, whereas chironomid community composition remained fairly stable before and after tephra deposition. Within the last 9085 years, enhanced local burning drove another increase in vegetation turnover. Terrestrial and freshwater ecosystems in Efate are sensitive to changes in hydroclimate, volcanism, and anthropogenic fires, although to different degrees; while recent human impacts are often obvious, volcanic eruptions and climatic shifts have also structured Pacific-island ecosystems and will continue to do so.